Competencia del mercado y su relación en el rendimiento económico en la cooperativa de taxi Cacharí de la ciudad de Babahoyo, período 2023. - Espín Montenegro, Darling Paul (2024)
The topic of this research is "Market competition and its relationship with economic performance in the Cachari cab cooperative in the city of Babahoyo, period 2023", for which the general objective is to analyze market competition and its relationship with economic performance in the Cachari Taxi Cooperative in the city of Babahoyo. The research method was inductive and deductive, applying a quantitative modality, of a basic non-experimental type. The technique used for the collection of information was the survey, which was executed in two levels, one in the form of an interview with the Manager of the Cachari Taxi Cooperative and the other in the form of a questionnaire to the citizens of Babahoyo, whose sample was 382 people. The results obtained showed that there is a lack of strategies for the development of a campaign to attract and retain users, as well as to generate a brand identity to improve the economic performance of the members of the cooperative, which has been undermined by formal and informal competition from other companies and cab cooperatives and even individuals. Concluding in the need to carry out a strategic plan that establishes a guide for the achievement of the institutional objectives, committed to the corporate mission and vision.